FOREIGNIZATION DALAM PENERJEMAHAN CULTURAL WORDS DARI BUKU JOHN BOYNE DENGAN JUDUL THE BOY IN THE STRIPED PYJAMAS - Ari Fajria Novari (Universitas Sultan Ageng Tirtayasa, 2017)
The aims of the study are to investigate the types of cultural words discovered in the novel and to investigate the translation procedures and foreignization approach used by the translator in translating the cultural words into Indonesian. A qualitative method was applied in this study. This method allowed the writer to make a systematic and factual description of the obtained data. The data were all the cultural words discover in the novel and a hundred of them were taken purposively. The data were categorized base on Newmark’s categories of cultural words (1988) namely ecology, material, social, and organization. The findings show that material was the most frequent category of cultural words found in the novel. Furthermore, from 100 cultural words translation, there are four out of ten strategies used in the framework of foreignization approach (Pedersen, 2005, Venuti, 1995, Judickaite, 2009). They are Preservation, Addition, Naturalization and Literal Translation. The findings show that Addition was the most frequent strategy used in the foreignization strategy in the novel. It means that the translator research making adding information in that SL it can be that the translate was strange transfer culture into TL culture, it does not TL culture. Based on the previous finding and discussion, the writer argues that the translation of The Boy in the Striped Pyjamas is easy to understand and may be readable by the Indonesian readers as the target readers since most of the cultural words has been translated well and well known by the Indonesian readers.